2008
DOI: 10.1371/journal.pone.0003141
|View full text |Cite
|
Sign up to set email alerts
|

Social Waves in Giant Honeybees Repel Hornets

Abstract: Giant honeybees (Apis dorsata) nest in the open and have evolved a plethora of defence behaviors. Against predatory wasps, including hornets, they display highly coordinated Mexican wave-like cascades termed ‘shimmering’. Shimmering starts at distinct spots on the nest surface and then spreads across the nest within a split second whereby hundreds of individual bees flip their abdomens upwards. However, so far it is not known whether prey and predator interact and if shimmering has anti-predatory significance.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
184
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(204 citation statements)
references
References 22 publications
12
184
2
Order By: Relevance
“…Signals observable at a distance allowed information to travel much faster than the ships could move themselves. Since these studies, similar behavioral cascades have been found in many other organisms (2,(6)(7)(8).…”
supporting
confidence: 72%
“…Signals observable at a distance allowed information to travel much faster than the ships could move themselves. Since these studies, similar behavioral cascades have been found in many other organisms (2,(6)(7)(8).…”
supporting
confidence: 72%
“…This decrease in brood area could be associated with the release of alarm pheromones that may change honeybee behavior, mainly by interfering with the flux of information transmitted by other pheromones in the colonies (Kastberger et al, 2008). Thus, the collecting of apitoxin could interfere with brood care, the queen's oviposition of worker eggs, and with resources collection by worker bees in some periods.…”
Section: Discussionmentioning
confidence: 99%
“…Giant honeybees (Apis dorsata) warn potential predators by producing shimmering movements. The signalling behaviour spreads from individual to individual, resulting in waves of movement across the entire (up to 1m-wide) comb (Kastberger et al, 2008). It has been suggested that termite drumming is more a warning signal aimed at vertebrate predators than an alarm signal (Howse, 1984).…”
Section: Recognition Of Pulse Structurementioning
confidence: 99%